Changes in the incidence of cervical lesions owing to the development of rheumatoid arthritis treatment and the impact of cervical lesions on patients' quality of life. Issue 3 (3rd May 2020) - Morita, Osamu; Miura, Kazuto; Hirano, Toru; Watanabe, Kei; Hanyu, Tadamasa; Netsu, Takahiro; Kondo, Naoki; Fujisawa, Junichi; Saeki, Takako; Ito, Tomoyuki; Shobugawa, Yugo; Yoshida, Kei; et al.
Abstract: Objectives: To clarify changes in the incidence of cervical lesions in rheumatoid arthritis (RA) patients with advanced treatment and the impact of cervical lesions on the patients' quality of life (QOL). Methods : Incidence of radiographic cervical lesions in 1333 RA patients in 2015 was compared with that in our 1999 survey. The association between cervical lesions and QOL evaluated using three different patient-based questionnaires was also analyzed. Results: The incidence of atlantoaxial subluxation (AAS), vertical subluxation (VS), and subaxial subluxation (SAS) in 2015 decreased by 50%, 75%, and 5%, respectively, compared to the 1999 survey. Although QOL, evaluated using the Japanese Orthopedic Association Cervical Myelopathy Evaluation Questionnaire (JOACMEQ; specific to myelopathy), deteriorated as the cervical lesion progressed, there was no association between cervical lesion progression and QOL evaluated using the Short Form-8™ (SF-8™; comprehensive health-related QOL). Cervical lesion progression was also associated with QOL deterioration evaluated using the Health Assessment Questionnaire Disability Index (HAQ-DI; specific to RA), but age and disease duration had stronger influences. Conclusion: The incidence of cervical lesions decreased in 2015 compared to 1999. Cervical lesion progression may be associated with QOL deterioration due to myelopathy. Age and disease duration have more impact on disease-specific QOL.